If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8a + 9b = cforb Solving 8a + 9b = bcfor Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-9b' to each side of the equation. 8a + 9b + -9b = -9b + bcfor Combine like terms: 9b + -9b = 0 8a + 0 = -9b + bcfor 8a = -9b + bcfor Divide each side by '8'. a = -1.125b + 0.125bcfor Simplifying a = -1.125b + 0.125bcfor
| 2.5=5-m | | 10p+9-11-p=4p+4-6p+6 | | 100d+45=115d | | k-6=3 | | y+4=-2(x-6) | | -16p-.04(2-5p)=.02(p-3)-.16 | | 5(6c-5)-(2(2c-3)+3)= | | X^2+3b-4=0 | | -11x+2=-15x+6 | | 6x=112 | | 6r+2=6 | | 54.8-.2d=60.1 | | 15c^2-3c= | | 54.8-.2=60.1 | | 2x-7y-10=o | | x^6y^6-x^5y^4+x^4y^3+x^3y^3=0 | | 0=-16t^2+14+2 | | 20x-110=-490 | | (-4)+-3(5)=-11 | | 7y+3=4 | | .008(3-k)+.09(k-2)=1 | | 3m-6=-33 | | 8x-4(5+2x)=12 | | m-9m-2m-6= | | 4x^3(7)= | | 7x-4+3x-6=90 | | 5x^2+3xy-2y^2= | | 2x+10=6x+12 | | 26x-28x=6-8 | | 6x+21y-26x+64y=0 | | (-2x^6y)(x^7y^5)= | | 9.3z-8.3z-7.2=-5.3+8.4 |